Implementasi Sistem Inferensi Fuzzy Pada Pengambilan Keputusan Penentuan Kualitas Air PDAM - Oktavia, S; Musdalifah, S; Lusiyanti, D (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
Water is one of the most important natural resources for all living things. For humans, water is used for bathing, washing and drinking so that the quality needs to be considered. Water quality is a major factor to determine the feasibility of water to be used. The purpose of this research is to implement Fuzzy inference system on decision making to determine water quality of PDAM. Mamdani method is used as a fuzzy inference systems and GUIDE MATLAB is used as a program that can facilitate the users. Input of the system in the form of values of water quality parameters test results the parameters are Color, Turbidity, Total Dissolved Solid (TDS), Nitrite, Nitrate, Coliform, e-coli, and pH. System works well in determining the quality of water, it can be evidenced by the level of accuracy of 94,44% of the 72 data used in Laboratory Uwe Lino Donggala District Laboratory and Palu District PDAM Laboratory